Analysis of Mangrove Vegetation (Rhizophora sp.) and Vertical Spesies of Fauna in Induha Village, Latambaga District, Kolaka Regency - Maretik Maretik; Sutriani Kaliu; Siska Siska (Jurnal Biologi Tropis, 2022)
Indonesian territory is dominated by Rhizophora mangrove vegetation, but in the Kolaka area, especially Induha Village, there is no information about this type of mangrove, so research is needed. The purpose of this study is to determine the vegetation Rhizophora mangroves sp. and fauna vertically in the mangrove forest in Induha Village. The method used is the Point Centered Sampling Method (PCQM). The results obtained, there are 3 types of mangrove Rhizophora namely Rhizophora apiculata, Rhizophora mucronata, and Rhizophora stylosa, with the highest relative density being Rhizophora apiculata at the seedling level (42.13%), sapling (57.50%) and at the tree level (38.31%). The highest relative frequency was Rhizophora apiculata at seedling (35%), sapling (45%) and tree (34.5%) levels. Rhizophora apiculata has the highest relative basal area value at the seedling (50%), sapling (84.83%) and tree (52.34%) levels. The highest relative canopy was Rhizophora apiculata, at the sapling (57.2%) and tree (35.3%). The highest Important Value Index was Rhizophora apiculata, at the seedling level (1 25.3 %), sapling (24 4.5 %) and tree (1 56.1 %). The fauna vertically identified as many as 5 types of species including hermit crabs, sea slugs, caterpillars, weaver ants and black ants. The conclusion of this study is that there are 3 types of mangroves identified in the mangrove forest dominated by Rhizophora apiculata and 5 fauna species. Environmental factors that have been observed support the survival of mangrove species in Induha Village, both in zone 1 and in zone 2, especially the Rhizophora apiculata.